2013
DOI: 10.5455/2319-2003.ijbcp20130314
|View full text |Cite
|
Sign up to set email alerts
|

Lornoxicam versus diclofenac sodium in acute renal colic: a prospective randomized trial

Abstract: Background: Acute renal colic is excruciatingly painful event, opioid analgesics and nonsteroidal anti-inflammatory drugs remain the mainstay of treatment for acute renal colic. This study compares diclofenac and lornoxicam in their efficacy to relieve pain of renal origin. Methods: Prospective, randomized, double blind clinical study including eighty patients with renal pain admitted in emergency department of a tertiary care teaching hospital. Parameters were observed at baseline and after 15, 30, 60, 180 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Similar to our study there are few studies available comparing the efficacy and safety of lornoxicam and diclofenac, Vishalkumar et al studied the efficacy and safety of lornoxicam and diclofenac in osteoarthritis knee patients the results showed that lornoxicam significantly relieved pain more than diclofenac [14]. Sushila godara et al conducted a study by comparing lornoxicam and diclofenac in the management of acute renal colic and concluded that both the drugs are equally effective and safe with added advantage of lornoxicam being more effective in the early period [15].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study there are few studies available comparing the efficacy and safety of lornoxicam and diclofenac, Vishalkumar et al studied the efficacy and safety of lornoxicam and diclofenac in osteoarthritis knee patients the results showed that lornoxicam significantly relieved pain more than diclofenac [14]. Sushila godara et al conducted a study by comparing lornoxicam and diclofenac in the management of acute renal colic and concluded that both the drugs are equally effective and safe with added advantage of lornoxicam being more effective in the early period [15].…”
Section: Discussionmentioning
confidence: 99%
“…Both nonsteroidal anti-inflammatory drugs (NSAIDs) and opioids are gold standards for relieving pain with acute renal colic (3,4). Although opioids are potent and cheap, they have some adverse events (AEs) such as nausea, vomiting, constipation, respiration depression (in larger doses), drowsiness, and hypotension (5). Compare with NSAIDS, opioid has fewer complications such as drowsiness, vomiting, and nausea; but it was demonstrated they can develop AEs such as nephropathy and platelet dysfunction (6).…”
Section: Introductionmentioning
confidence: 99%
“…Although opioids are cheap and potent and can be easily titrated but they have various adverse effects as constipation, drowsiness, nausea, and vomiting, larger doses lead to depression of respiration, hypotension, and drug seeking behavior presenting as renal colic [ 5 ].…”
Section: Introductionmentioning
confidence: 99%